Immunohistochemistry for YAP1 N-terminus and C-terminus highlights metaplastic thymoma and high-grade thymic epithelial tumors by different staining patterns - Yamada, Yosuke; Küffer, Stefan; Sauer, Christian; Hoki, Masahito; Shibuya, Shinsuke; Tsujii, Hideaki; Ono, Kazuo; Moriyoshi, Koki; Date, Hiroshi; Yoshizawa, Akihiko; Szolkowska, Malgorzata; Haga, Hironori; et al. (Virchows Archiv, 2024)
Metaplastic thymoma (MT), a rare subtype of thymic epithelial tumors (TETs), harbors YAP1::MAML2 fusions. Poroma, a skin tumor, also carries these fusions and exhibits a unique staining pattern for YAP1 immunohistochemistry (IHC), namely, a YAP1 N-terminus (YAP1[N])-positive but YAP1 C-terminus (YAP1[C])-negative pattern. In this context, MT was recently reported to lack YAP1(C) expression exclusively among TET subtypes. However, a lack of information about YAP1(N) expression in that study and another report that wild-type YAP1 expression was diminished in type B3 thymoma and thymic carcinoma warrants further studies for YAP1 expression in TETs. Thus, we immunohistochemically examined YAP1(N) and YAP1(C) staining patterns in our TET samples, including 14 cases of MT. In addition, 11 of the 14 MT cases were genetically analyzed with the formalin-fixed paraffin-embedded tissues if they harbored YAP1::MAML2 fusions. MT consistently exhibited YAP1(N)-positive and YAP(C)-negative staining, whereas type B3 thymoma and thymic carcinoma showed relatively heterogeneous staining patterns for YAP1(N) and YAP1(C) and were sometimes negative for both antibodies. Furthermore, a lower expression of YAP1 was found in type B3 compared to B2 thymomas. Among genetically analyzed 11 MT cases, 6 cases showed YAP1::MAML2 fusions, whereas the analysis failed in 5 very old cases due to poor RNA quality. These results indicate that IHC of both YAP1(N) and YAP1(C) is recommended to obtain staining patterns almost unique to MT. The biological significance of YAP1 in high-grade TETs warrants further investigation.